2023
DOI: 10.3389/fonc.2023.1091118
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-dependent ferroptosis as a potential treatment for glioblastoma

Abstract: Glioblastoma (GBM) is the most common malignant primary brain tumor with a poor 5-year survival rate. Autophagy is a conserved intracellular degradation system that plays a dual role in GBM pathogenesis and therapy. On one hand, stress can lead to unlimited autophagy to promote GBM cell death. On the other hand, elevated autophagy promotes the survival of glioblastoma stem cells against chemotherapy and radiation therapy. Ferroptosis is a type of lipid peroxidation-mediated regulated necrosis that initially di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Other less conventional pathways of RCD can be triggered along with autophagic flux. For example, Gupta et al showed that induction of mitophagy as well as oxidative and proteotoxic stresses by CuO NPs led to the induction of cuproptosis, a form of RCD that triggered by the accumulation of Cu in mitochondria [ 192 ].In addition, iron oxide NPs can be inducers of autophagy-dependent ferroptosis, a form of RCD that is driven by iron-dependent phospholipid peroxidation through the activation of autophagy machinery [ 193 ]. In this case, ultrasmall iron oxide (USIO) NPs have been applied for glioblastoma cells to induce ferroptosis via a Beclin1/ATG5-dependent autophagy pathway by increasing the intracellular iron level, catalysing Fenton reaction, generating ROS and lipid peroxidation [ 194 ].…”
Section: Nanomaterials Induce Pro-survival or Pro-death Autophagy?mentioning
confidence: 99%
“…Other less conventional pathways of RCD can be triggered along with autophagic flux. For example, Gupta et al showed that induction of mitophagy as well as oxidative and proteotoxic stresses by CuO NPs led to the induction of cuproptosis, a form of RCD that triggered by the accumulation of Cu in mitochondria [ 192 ].In addition, iron oxide NPs can be inducers of autophagy-dependent ferroptosis, a form of RCD that is driven by iron-dependent phospholipid peroxidation through the activation of autophagy machinery [ 193 ]. In this case, ultrasmall iron oxide (USIO) NPs have been applied for glioblastoma cells to induce ferroptosis via a Beclin1/ATG5-dependent autophagy pathway by increasing the intracellular iron level, catalysing Fenton reaction, generating ROS and lipid peroxidation [ 194 ].…”
Section: Nanomaterials Induce Pro-survival or Pro-death Autophagy?mentioning
confidence: 99%
“…However, in contrast to HSPA8, heat shock protein family A member 5 (HSPA5) inhibits degradation of GPX4 by interacting with GPX4, thereby inhibiting ferroptosis (Li et al 2021a ). Mitophagy also plays an important role in ferroptosis (Xie et al 2023 ). Classic mitophagy pathways include PTEN-induced kinase 1 (PINK1)/ parkin RBR E3 ubiquitin protein ligase (Parkin), Bcl-2 19-kDa interacting protein 3 (BNIP3)/ NIP3-like protein X (Nix) and FUN14 domain containing 1 (FUNDC1) pathway (Ajoolabady et al 2022 ).…”
Section: Subcellular Organelles Drive Ferroptosis (Fig 2 ...mentioning
confidence: 99%